2017
DOI: 10.3171/2017.5.focus17153
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive direct pars repair with cannulated screws and recombinant human bone morphogenetic protein: case series and review of the literature

Abstract: OBJECTIVEThe objective of this study was to describe the use of a minimally invasive surgical treatment of lumbar spondylolysis in athletes by a fluoroscopically guided direct pars screw placement with recombinant human bone morphogenetic protein–2 (rhBMP-2) and to report on clinical and radiographic outcomes.METHODSA retrospective review was conducted of all patients treated surgically for lumbar spondylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In 4 series, the authors used a minimally invasive approach for the Buck repair. 10,12,21,51 Three studies used bone morphogenetic protein (BMP) to aid the fusion. Eight studies used pedicle screws with laminar hooks, and 4 studies used pedicle screws with a wiring technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 4 series, the authors used a minimally invasive approach for the Buck repair. 10,12,21,51 Three studies used bone morphogenetic protein (BMP) to aid the fusion. Eight studies used pedicle screws with laminar hooks, and 4 studies used pedicle screws with a wiring technique.…”
Section: Resultsmentioning
confidence: 99%
“…BMP was used to aid fusion in 3 studies. 10,21,46 All of these studies reported good fusion rates. Analysis of the data from this study has shown that in patients with spondylolysis and low-grade spondylolisthesis in whom conservative treatment has failed, surgical management substantially improves the outcome and return to activity.…”
Section: Pedicle Screw-based Repairsmentioning
confidence: 96%
See 1 more Smart Citation
“…37 In our cohort, based on previous literature, we only used 1 mg rhBMP-2 as a dual-use drug, which was much lower than the dose used in the previous study for intervertebral fusion. 28,31,32 This may explain the lack of complications. Our findings indicate that the use of 1 mg rhBMP-2 in pars repair is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Goldstein et al used cortical screws and a spinous-process modular link in a minimally invasive fashion under intraoperative CT navigation [ 26 ]. Ghobrial et al treated lumbar spondylolysis via a minimally invasive direct pars repair with cannulated screws [ 27 ].…”
Section: Discussionmentioning
confidence: 99%